'n Vergelyking tussen die afronding van beeste op anthephora pubescens en natuurlike veld in die Vryburg-omgewing - Knight, Ian Wesley (Bloemfontein: Central University of Technology, Free State, 2001)
An comparison between the fattening potential of cattle onAnthephorapubescens and natural veld in the Vryburg region The fattening potential of Anthephora pubescens was investigated with one-year and two-year oxen and compared to natural pasture. On Anthephora pubescens animal mass twice-weekly obtained, as well as, cold carcass mass, grading, growth and production data, climatological data, crude protein and digestibility, voluntary feed intake and economical viability. The available pasture, crude protein and digestibility, twice-weekly animal mass, cold carcass mass, grading and the economy were determined on veld. The project period was characterised by a low average annual rainfall of355 mm, in comparison to the long-term average of 432 mm. On grass and veld pasture the average daily gain of the oneyear oxen was 1. 102 en 0.899 gram per day, while that of the two-year oxen was respectively 1.129 and 1.000 gram daily. A statistical analysis of the average daily gain showed significant differences between season and age and group and season. Average dry matter production ofthe bottlebrush pasture was 1 900 kglha. On average, the fattening periods of both groups of oxen on grass and veld pasture were 108 and 109 days respectively. On bottle brush pasture the average stocking rate was 2.20 ha/LSU and that of veld 15.60 ha/LSU for the trial period. The stocking rate on veld was exceptionally low due to a calculation error. Voluntary intake ofboth groups of oxen were satisfactory on the bottle grass pasture. During the trial period the crude protein, digestibility and dry organic matter ofboth pastures were quite low. Carcass grading on the grass pasture was better than on veld. Economically, the grass pasture had a higher gross margin per hectar than veld. Veld pasture had better gross margins per LSU, one-year oxen and two-year oxen during the trial period. The fattening potential of Anthephora pubescens can be highly esteemed in the Vryburg region. This crop had a high production, is adaptable, high grading is possible with Bonsmara oxen and compared well with veld pasture. The conversion of marginal soils into veld with planted pastures like bottlebrush should be very popular, as planted pastures can be economically viable with good management. The risk of fattening oxen in this area is increased by the unreliable rainfall.
Thesis
Keywords: Beef cattle; Anthephora pubescens; Grasses - South Africa - North-West Province